Causes of fever in primary care in Southeast Asia and the performance of C-reactive protein in discriminating bacterial from viral pathogens. (July 2020) - Althaus, Thomas; Thaipadungpanit, Janjira; Greer, Rachel C.; Swe, Myo Maung Maung; Dittrich, Sabine; Peerawaranun, Pimnara; Smit, Pieter W.; Wangrangsimakul, Tri; Blacksell, Stuart; Winchell, Jonas M.; Diaz, Maureen H.; Day, Nicholas P.J.; et al.
Highlights: Evidence on causes of fever is limited in Southeast Asia, especially in primary care. Point-of-care diagnostic tools could guide health workers' antibiotic prescription. C-reactive protein was significantly increased in cases of bacterial infections. Most primary care patients recovered regardless of antibiotic prescription. Antibiotic prescription should be an exception in the primary levels of care. Abstract: Objectives: This study investigated causes of fever in the primary levels of care in Southeast Asia, and evaluated whether C-reactive protein (CRP) could distinguish bacterial from viral pathogens. Methods: Blood and nasopharyngeal swab specimens were taken from children and adults with fever (>37.5 °C) or history of fever (<14 days) in Thailand and Myanmar. Results: Of 773 patients with at least one blood or nasopharyngeal swab specimen collected, 227 (29.4%) had a target organism detected. Influenza virus type A was detected in 85/227 cases (37.5%), followed by dengue virus (30 cases, 13.2%), respiratory syncytial virus (24 cases, 10.6%) and Leptospira spp. (nine cases, 4.0%). Clinical outcomes were similar between patients with a bacterial or a viral organism, regardless of antibiotic prescription. CRP was higher among patients with a bacterial organism compared with those with a viral organism (median 18 mg/L, interquartile range [10–49] versus 10 mg/L [≤8–22], p = 0.003), with an area under the curve of 0.65 (95% CI 0.55–0.75). Conclusions: Serious bacterial infections requiring antibiotics are an exception rather than the rule in the first line of care. CRP testing could assist in ruling out such cases in settings where diagnostic uncertainty is high and routine antibiotic prescription is common. The original CRP randomised controlled trial was registered with ClinicalTrials.gov, number NCT02758821.